The effects of pneumoperitoneum and patient position on the perfusion index and pleth variability index during laparoscopic bariatric surgery - ARSLANTAŞ, MUSTAFA KEMAL; ÇORMAN DİNÇER, PELİN (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: Limited data are available on the use of the perfusion index (PI) and the pleth variability index (PVI) during laparoscopic bariatric suigery. We investigated the effects of pneumoperitoneum and the reverse Trendelenburg position on these indices. Materials and Methods: PI, PVI, heart rate (HR), blood pressure, SpO(2) and ventilation parameters were recorded before anaesthesia induction (T0), 5 min after endotracheal intubation (T1), immediately before surgery, after the patient had been in the reverse Trendelenburg position for 5 min (T2), after inflating the abdomen with CO2 in reverse Trendelenburg (T3), after the abdomen had been deflated (T4) and 5 min after extubation (T5). Results: General anaesthesia induced an increase in the PI (P<.001), and a decrease in the PVI (P=.002). The PI and PVI values were not affected during T2 or T3. Pneumoperitoneum caused an increase in mean arterial pressure (MAP) and a decrease in HR. PVI and MAP decreased during 14, but the PI and IHR remained unchanged. PVI, HR and MAP increased during T5. Conclusion: Our data suggest that the reverse Trendelenburg position and pneumoperitoneum did not affect the PI or PVI values, whereas deflation decreased the PVI in morbidly obese patients under general anaesthesia.
Keywords: Anaesthesia; Morbid obesity; Pleth variability index; Perfusion index; Bariatric surgery; STROKE VOLUME VARIATION; DIRECTED FLUID THERAPY; Y GASTRIC BYPASS; DYNAMIC VARIABLES; INTRAABDOMINAL PRESSURE; GENERAL-ANESTHESIA; RESPONSIVENESS; OBESITY